Peningkatan Kualitas Hidup Pasien Stroke Melalui Discharge Planning - Anwar Saifudin; Titi Hartiti; Vivi Yosafianti Pohan (FORIKES, 2024)
Stroke is the second leading cause of death and the third leading cause of disability and is the second most common non-communicable disease causing death in the world after ischemic heart disease. Improving quality of life is the main goal expected in post-hospitalization stroke patient care. Discharge planning in stroke patients is a plan carried out for patients and families before patients leave the hospital in order to achieve optimal health and improve quality of life. The purpose of this study was to determine the effect of discharge planning on the quality of life of stroke patients. This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) method using several databases, namely Google Scholar, PubMed, ScienceDirect which are relevant in the last 6 years (2019-2024) with the keywords discharge planning, quality of life and stroke. This systematic review used 8 articles that meet the inclusion criteria. The results of the review showed that providing discharge planning to families and stroke patients can have a good impact on increasing family readiness in caring for patients so that patients can achieve optimal health and improve quality of life. Based on the results of the review, it was concluded that the implementation of discharge planning has an effect on improving the quality of life of stroke patients.Keywords: discharge planning; quality of life; stroke ABSTRAK Stroke menjadi penyebab utama nomor dua kematian serta nomor tiga kecacatan serta merupakan penyakit tidak menular yang terbanyak menyebabkan kematian kedua di dunia setelah penyakit jantung iskemik. Peningkatan kualitas hidup merupakan tujuan utama yang diharapkan dalam perawatan pasien stroke pasca rawat inap. Discharge planning pada pasien stroke merupakan perencanaan yang dilakukan untuk pasien dan keluarga sebelum pasien meninggalkan rumah sakit agar dapat mencapai kesehatan yang optimal dan meningkatkan kualitas hidup. Tujuan dari studi ini adalah untuk mengetahui pengaruh discharge planning terhadap kualitas hidup pasien stroke. Studi ini menggunakan metode Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) dengan menggunakan beberapa database yaitu Google Scholar, PubMed, ScienceDirect yang relevan dalam 6 tahun terakhir (2019-2024) dengan kata kunci discharge planning, kualitas hidup dan stroke. Systematic review ini menggunakan 8 artikel yang sesuai dengan kriteria inklusi. Hasil review menunjukkan bahwa pemberian discharge planning pada keluarga dan pasien stroke dapat memberikan dampak yang baik dalam meningkatkan kesiapan keluarga dalam merawat pasien sehingga pasien dapat mencapai kesehatan yang optimal serta meningkatkan kualitas hidup. Berdasarkan hasil review disimpulkan bahwa penerapan discharge planning berpengaruh terhadap peningkatan kualitas hidup pasien stroke.Kata kunci: discharge planning; kualitas hidup; stroke